From the political pipe to devil eyes: a history of the British election poster from 1910-1997 - Burgess, Christopher (2014)
Despite their use in every British general election of the twentieth and twentieth first century, the political poster remains largely unconsidered by the majority of historians working in the field of British politics. This thesis is the first study dedicated entirely to the posters role in British elections. Through five election case studies, the work contextualises the poster within the broader narratives of election culture. Unusually for studies of political communication, it is the type and content of the communication – namely the poster – that forms the central focus of each chapter. Each of which seeks to locate the production, content and display of posters parties produced for an election, within the broader landscape of that elections particular culture.